A study of the mediating effect of social support on self-disclosure and demoralization in Chinese older adult homebound breast cancer patients - Liu, Meifeng; Qin, Fawei; Wang, Deyu (Frontiers in Psychology, 2024)
Purpose: Demoralization is common in older adult homebound breast cancer patients, seriously affecting their quality of life. This study aimed to investigate the demoralization of older adult homebound breast cancer patients and to analyse the mediating effects of social support between self-disclosure and demoralization.2Methods: The study enrolled 368 older adult homebound breast cancer patients reviewed in outpatient clinics of three hospitals from January 2022 to August 2023. A questionnaire survey was conducted using the general information questionnaire, the distress disclosure index (DDI), the social support revalued scale (SSRS), and the demoralization scale (DS). Path analysis was conducted to test the hypothesised serial mediation model.3The total scores of self-disclosure, social support, and demoralization were 37 (25-42), 34 (19-48.75), and 46.5 (35-68), respectively. The results indicated a positive correlation between self-disclosure and social support (P < 0.01). In contrast, a statistically significant negative correlation was observed between self-disclosure, social support, and various demoralization dimensions (P < 0.01). Social support played a partial mediation effects between self-disclosure and demoralization, indirect effect =0.6362, SE = -0.591, 95% CI( -0.785~-0.415);Self-disclosure direct effect demoralization,direct effect =0.3638, SE = -0.337, 95% CI (-0.525~-0.144);total effect , SE =-0.929,95% CI ( -0.945~-0.904).